Cardiac cachexia: hic et nunc. Issue 3 (1st July 2016) - Loncar, Goran; Springer, Jochen; Anker, Markus; Doehner, Wolfram; Lainscak, Mitja
Abstract: Cardiac cachexia (CC) is the clinical entity at the end of the chronic natural course of heart failure (HF). Despite the efforts, even the most recent definition of cardiac cachexia has been challenged, more precisely, the addition of new criteria on top of obligatory weight loss. The pathophysiology of CC is complex and multifactorial. A better understanding of pathophysiological pathways in body wasting will contribute to establish potentially novel treatment strategies. The complex biochemical network related with CC and HF pathophysiology underlines that a single biomarker cannot reflect all of the features of the disease. Biomarkers that could pick up the changes in body composition before they convey into clinical manifestations of CC would be of great importance. The development of preventive and therapeutic strategies against cachexia, sarcopenia, and wasting disorders is perceived as an urgent need by healthcare professionals. The treatment of body wasting remains an unresolved challenge to this day. As CC is a multifactorial disorder, it is unlikely that any single agent will be completely effective in treating this condition. Among all investigated therapeutic strategies, aerobic exercise training in HF patients is the most proved to counteract skeletal muscle wasting and is recommended by treatment guidelines for HF.